22nd EURL-Salmonella interlaboratory comparison study (2017) on typing of Salmonella spp - Jacobs-Reitsma, WF; Verbruggen, A; Bouw, E; Mooijman, KA (Rijksinstituut voor Volksgezondheid en Milieu, 2018)
The National Reference Laboratories (NRLs) of all 28 European Union (EU) Member States performed well in the 2017 quality control test on Salmonella typing. Overall, the EU-NRLs were able to assign the correct name to 98% of the strains tested. In addition to the standard method for typing Salmonella (serotyping), fifteen laboratories performed typing at DNA level using Pulsed Field Gel Electrophoresis (PFGE). This more detailed typing method is sometimes needed to trace the source of a contamination. For quality control, participants received another eleven strains of Salmonella to be tested by this method. Eleven of the fifteen participating laboratories were suitably equipped to use the PFGE method. Since 1992, the NRLs of the EU Member States are obliged to participate in annual quality control tests which consist of interlaboratory comparison studies on Salmonella. Each Member State designates a specific laboratory within their national boundaries to be responsible for the detection and identification of Salmonella strains in animals and/or food products. These laboratories are referred to as the National Reference Laboratories (NRLs). The performance of these NRLs in Salmonella typing is assessed annually by testing their ability to identify 20 Salmonella strains. NRLs from countries outside the European Union occasionally participate in these tests on a voluntary basis. The EU-candidate-countries Former Yugoslav Republic of Macedonia and Serbia, EFTA countries Iceland, Norway and Switzerland, and Israel took part in the 2017 assessment. The annual interlaboratory comparison study on Salmonella typing is organised by the European Union Reference Laboratory for Salmonella (EURL-Salmonella). The EURL-Salmonella is located at the National Institute for Public Health and the Environment (RIVM), Bilthoven, the Netherlands.